KEPUASAN PESERTA PELATIHAN JARAK JAUH TERHADAP LAYANAN VIDEO TUTORIAL CARA MENGOPERASIKAN LMS BERBASIS MOODLE - Dedi Restendi (JENTRE, 2021)
This study aims to determine the level of satisfaction of distance training participants (PJJ) with video tutorial services on how to operate a Moodle-based learning management system. One of the reasons for the success of participants in participating in remote training is their technical ability to operate the Bandung Religious Education and Training Center's PJJ application. The satisfaction of remote training participants is a reflection of the quality of video tutorial services produced as an effort to serve participants who have difficulty operating the learning management system. descriptive, namely analyzing the satisfaction of PJJ participants on the dimensions of reliability, tangibles and Responsiveness to video tutorials containing technical explanations for operating a moodle-based learning management system which is the application platform for the Bandung Religious Education and Training Center PJJ application platform. Population and Sample The population of this research is the participants of the long distance training at the Bandung Religious Education and Training Center in 2021, with a total of 800 participants. The sample in question is the object under study is the participants who are taken as respondents from this study. The results showed that the training participants were very satisfied with the video tutorial service. Video tutorial services have reliability and are in accordance with the needs and expectations of participants, which can be seen repeatedly, owned and felt by participants as in the second dimension, namely tangible. Regarding the Quick Response variable, the video tutorial service is able to respond to complaints from PJJ participants who have difficulty operating a moodle-based learning management system. Keywords: Video tutorials; Satisfaction; PJJ.